Vários pesos, várias medidas: análise crítica do discurso da mídia em manchetes políticas de capas dos jornais Folha de S. Paulo, O Globo e Jornal do Commercio entre 2015 e 2018. - Santos, Leusa Cristina Bezerra dos (2018)
The period between 2014 and 2018 in Brazil registered political scandals, political and economic crisis, recession and unemployment. In this period, the facts linked to these events had emphasis in the media across the country. Newspapers, radios, TVs were and still being stage of dissemination and broadcasting about (a) Dilma Rousseff impeachment and the political fights that occurred in the streets and the parliament during and after the mandate of the presidente. (b) prison, delations, condemnations from the Lava Jato Operation; (c) scandals that striked Temer's administration and (d) negative results about brasilian economy numbers that suffered Gross National Product (GNP) resurgence and growth unemployment indications and (d) the arrest of the ex-president Lula. All these facts did not follow in chronological order, but, are intertwined in social economic Brazil conjuncture. And are the main journalistic subject of media communication that, acting simultaneously in a clash arena to gain audience and establish discursive credibility, reverberate this events. Based in this social political contexts, this thesis has a main purpose understand how the newspapers analyze articulate linguistic, discursive and social meanings in the headlines about political and economic crisis themes. For this, we investigate the significations produced by the media: if there is a mere reproduction of facts that engender audience in specifics moments or encourage some reflexion about the power relations. The base theory to this paper is the Critical Discourse Analisys (CDA), whose main foundation theoretical is Fairclough (1992, 1995, 2001, 2004) and Chouliaraki and Fairclough (1999), in adittion to Charaudeau (2006, 2010, 2011) in the construction of the theories. The work was also constructed with relevant historical, conceptual and reflective contributions of Jenkins (2009), Ramalho and Resende (2004), Schwarcz and Starling (2015), Wodak (2004) among other authors. The qualitative research and documentary approach has as corpus extended the headlines of newspaper covers on subjects related to the political and economic crises of two national newspapers - Folha de S. Paulo and O Globo - and one from the state of Pernambuco - journal between January 2015 and April 2018. The analysis of the discursive media practices in the statements about the political and economic crises was focused, with the text - verbal and non-verbal - as the first support for the investigation from the three-dimensional model of Fairclough (2001), which allows a textual, discursive and social approach to the object under study, as well as reflections on social practice. We perceive that: I) the newspapers analyzed reproduced the discourses of the events that occurred, creating among these facts a "temporal intertextuality", which discursively encloses events even though they are not directly linked; II) even if temporally linked, there was a differentiation of the discursive treatment of the media to Dilma Rousseff / Lula and Temer, the first two being vilanized and the second, in spite of being also involved in corruption, was discursively minimized on the accusations; III) the vehicles also fed a discursive narrative that orbited homogeneously in certain subjects "of the moment" (RAMALHO AND RESENDE, 2004): political and economic crises, impeachment, prisons, awards awards, etc. stimulate a critical debate, despite the traditional media still being the vehicle that brings more reliability, according to Ibope research. There were, therefore, no discursive marks in the headlines that pointed to an in-depth analysis of events, one of the rules of journalistic making (PENA, 2008). This discursive omission contributed and, in our view, contributed to support the still hegemonic assimilation of an apparently linear scenario of the Brazilian politico-social context. In this way, media vehicles have absorbed and constituted the social practice of the economic crisis, emphasizing negative characteristics of events, to the detriment of an interpretive perspective of origin, cause and consequences of the facts produced by the hegemonies that have passed relatively in power: State, Federal Police and political and business segments.